Bringing pronunciation back into the ESL/EFL classroom: Current research trends and recommendations for teachers and teacher trainers - Zárate-´Sández, Germán (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2021)
Pronunciation instruction in English as a second/foreign language classes has often been limited or outright ignored in communicative approaches to second language (L2) teaching. In parallel, pronunciation research in the last two decades has witnessed a major paradigm shift driven by the premise that learners’ speech needs to be intelligible and not necessarily native-like. L2 pedagogy, however, has not taken full advantage of the substantial body of research produced under this approach. The goals of this paper, therefore, are to bridge the gap between scholars and practitioners and to make recommendations for teachers and teacher trainers. The paper reviews the effectiveness of pronunciation instruction, synthesizes research on what aspects of English pronunciation should be taught and how, and examines English teachers’ cognitions, beliefs, and training in pronunciation instruction. The last section discusses learners’ goals and identities regarding English pronunciation within the English as a Lingua Franca framework.